2008
DOI: 10.1590/s0102-86502008000500014
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound evaluation of techniques for internal jugular vein puncture in children

Abstract: Purpose:To determine by ultrasound which access and position the child must stay to obtain the best transversal section of the right Internal Jugular Vein (RIJV) allowing a safer puncture. Methods: Three possible accesses to the RIJV, anterior, lateral and posterior, from 57 healthy children, were analyzed through ultrasound images in a sequence of positions of the head, in supine position, with or without a roll under the scapula: head centered in neutral position with and without a roll (NPP and NP); contra … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…The Trendelenburg position is the most preferred because it increases venous return and IJV diameter. 17 It also reduces the risk of air embolism. 1 , 5 , 8 Apart from this, the Valsalva manoeuvre and hepatic compression are used to increase the venous return and IJV diameters.…”
Section: Discussionmentioning
confidence: 99%
“…The Trendelenburg position is the most preferred because it increases venous return and IJV diameter. 17 It also reduces the risk of air embolism. 1 , 5 , 8 Apart from this, the Valsalva manoeuvre and hepatic compression are used to increase the venous return and IJV diameters.…”
Section: Discussionmentioning
confidence: 99%
“…Position of the head and the landmarks chosen for IJV access has been shown by Schettini and Coll (14) and Ybarra and Coll (21) to influence the diameter of IJV, which in turns influence the difficulties in catheterization. Interestingly, the best position was not that classically used during IJV canulation in children (the contra lateral rotation of the head with a roll under the shoulder) but the neutral position without a roll and in the Trendelenburg position (14,21). The classical position described during adult IJV access used in all included studies might not be the most suitable in children and infants.…”
Section: Discussionmentioning
confidence: 99%
“…The smaller dimension of IJV in children increases the number of attempts; favors the changes in puncture points and the depth of needle insertion; and finally increases the risks of complications such as carotid artery puncture or pneumothorax. Second, many ultrasound studies have found variations in IJV position relative to the common carotid artery, with the IJV being anterior to the carotid artery in many cases (1,14–16). This position might also increase the risks of carotid artery puncture.…”
Section: Discussionmentioning
confidence: 99%
“…The Seldinger technique was used for venous puncture [20] in association with the split sheath technology. For implantations in the internal jugular vein, the puncture was carried out at the medial edge of the clavicular head of the sternocleidomastoid muscle, two centimeters above the upper edge of the clavicle [21,22]. For implantations into the subclavian vein, the puncture parameter was the midpoint of the clavicle.…”
Section: Methodsmentioning
confidence: 99%